Chemistry of sustainable energy - Carpenter, Nancy E. (CRC Press/Taylor and Francis, 2014)
Understanding the chemistry underlying sustainable energy is central to any long-term solution to meeting our future energy needs. Chemistry of Sustainable Energy presents chemistry through the lens of several sustainable energy options, demonstrating the breadth and depth of research being carried out to address issues of sustainability and the global energy demand. The author, an organic chemist, reinforces fundamental principles of chemistry as they relate to renewable or sustainable energy generation throughout the book. Written with a qualitative, structural bias, this su.